Autopsy‐confirmed hippocampal‐sparing Alzheimer's disease with delusional jealousy as initial manifestation. Issue 3 (3rd March 2015) - Fujishiro, Hiroshige; Iritani, Shuji; Hattori, Miho; Sekiguchi, Hirotaka; Matsunaga, Shinji; Habuchi, Chikako; Torii, Youta; Umeda, Kentaro; Ozaki, Norio; Yoshida, Mari; Fujita, Kiyoshi
Abstract Alzheimer's disease (AD) is clinically characterized by gradual onset over years with worsening of cognition. The initial and most prominent cognitive deficit is commonly memory dysfunction. However, a subset of AD cases has less hippocampal atrophy than would be expected relative to the predominance of cortical atrophy. These hippocampal‐sparing cases have distinctive clinical features, including the presence of focal cortical clinical syndromes. Given that previous studies have indicated that severe hippocampal atrophy corresponds to prominent loss of episodic memory, it is likely that memory impairment is initially absent in hippocampal‐sparing AD cases. Here, we report on a patient with an 8‐year history of delusional jealousy with insidious onset who was clinically diagnosed as possible AD and pathologically confirmed to have AD with relatively preserved neurons in the hippocampus. This patient had delusional jealousy with a long pre‐dementia stage, which initially was characterized by lack of memory impairment. Head magnetic resonance imaging findings showed preserved hippocampal volume with bilateral enlarged ventricles and mild‐to‐moderate cortical atrophy. Head single‐photon emission computed tomography revealed severely decreased regional cerebral blood flow in the right temporal lobe. The resolution of the delusion was attributed to pharmacotherapy by an acetylcholinesterase inhibitor, suggesting that the occurrence of delusional jealousy was due to the disease process of AD. Although the neural basis of delusional jealousy remains unclear, this hippocampal‐sparing AD case may be classified as an atypical presentation of AD.